Ratio of interventricular septal thickness to global longitudinal strain accurately identifies cardiac amyloidosis - Jignesh Patel; I-Min Chiu; David Ouyang; Michael Abiragi; Louie Cao; Jonathan Le; Chathuri Daluwatte; Piero Ricchiuto; Gloria J Hong; P Ryan Tacon; Lily K Stern (Open Heart)
Objectives Conventional transthoracic echocardiographic measurements like global longitudinal strain (GLS) have shown promise in distinguishing cardiac amyloidosis (CA), but with limited specificity. We investigated the performance of common echo measurements, GLS, and their combinations in discriminating CA from an undifferentiated cohort with increased left ventricular wall thickness.Methods We conducted a retrospective single-centre case–control study of 876 echos from 232 patients with CA and 1325 echos from 279 patients who underwent pyrophosphate scintigraphy but had CA definitively ruled out. Common echo measurements were collected and additional GLS measurements were performed post hoc. We reported discrimination performance with the area under the receiver operating characteristic curve (AUC) and associated sensitivity, specificity and positive predictive value at the optimal threshold.Results We found that the ratio of end-diastolic interventricular septal thickness (IVSd) to GLS had the highest performance in differentiating CA with an AUC of 0.812. At the optimal threshold of >0.15, IVSd/GLS had a sensitivity of 0.70 and specificity of 0.80 for CA. Other measurements and ratios, including the ratio of left ventricular ejection fraction to GLS (AUC 0.682), had lower performance when evaluated against a suspicious control cohort with increased left ventricular wall thickness.Conclusion If validated in prospective multi-centre studies, the routine measurement of IVSd/GLS can assist with earlier diagnosis of CA, resulting in earlier initiation of treatment in this underserved population.